HUBUNGAN YANG SIGNIFIKAN ANTARA KOMUNIKASI INTERPERSONAL ANAK DENGAN ORANG TUA TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 106143 SUKA MAJU TAHUN AJARAN 2019/2020 - Eti Muliani; Juwita Tindaon (Universitas Negeri Medan, 2020)
Abstract: The Relationship Between Interpersonal Communication of Children and Parents Against Social Studies Learning Outcomes of Class V Elementary School Students 106143 Like Advanced Academic Year 2019/2020. This study aims to determine the relationship between children's interpersonal communication and their parents on the science learning outcomes of Class V Elementary School Students 106143 Suka Maju Academic Year 2019/2020. This research is a kind of correlation research. The population in this study amounted to 27 grade V students of State Elementary School 106143 Suka Maju, and the sample in this study 27 Grade V students of State Elementary School 106143 Suka Maju because the sampling technique was the total sample. Data collection tools used questionnaires and documentation of mid-semester report cards in August. In the questionnaire, there are four answer choices and scoring techniques based on the Liker scale, namely 1-4. Where is the value r = 0,53 n =27 = 0,282 and dk = 25. Then the value is obtained = 3,134, terms of accept H1 if > to = 2,06 can be seen from the t value distribution table. Then > so accept so accept H1 or there is a significant relationship between interpersonal communication between children and parents on social studies learning outcomes of class V elementary school students 106143 Suka Maju. Keywords: Interpersonal Communication, Social Studies Learning OutcomesAbstrak: Hubungan Yang Signifikan Antara Komunikasi Interpersonal Anak Dengan Orang Tua Terhadap Hasil Belajar IPS Siswa Kelas V SD Negeri 106143 Suka Maju Tahun Ajaran 2019/2020. Penelitian ini bertujuan untuk mengetahui hubungan komunikasi interpersonal anak dengan orang tua terhadap hasil belajar IPA Siswa Kelas V SD Negeri 106143 Suka Maju Tahun Ajaran 2019/2020. Penelitian ini merupakan jenis penelitian kolerasi. Populasi dalam penelitian ini berjumlah 27 orang siswa kelas V SD Negeri 106143 Suka Maju, dan sampel dalam penelitian ini 27 orang siswa kelas V SD Negeri 106143 Suka Maju karena teknik pengambilan sampel merupakan sampel total. Alat pengumpulan data menggunakan angket dan dokumentasi nilai raport pertengahan semester pada bulan Agustus. Pada angket terdapat empat pilihan jawaban dan teknik pemberian skor berdasarkan skala Liker, yaitu 1-4. Dimana nilai r = 0,53 n =27 = 0,282 dan dk = 25. Maka diperoleh nilai = 3,134, syarat terima H1 jika > , untuk = 2,06 bisa dilihat dari tabel distribusi nilai t. Maka > sehingga terima sehingga terima H1 atau ada hubungan yang signifikan antara komunikasi interpersonal anak dengan orangtua terhadap hasil belajar IPS siswa kelas V SD Negeri 106143 Suka Maju. Kata Kunci: Komunikasi Interpersonal, Hasil Belajar IPS